War as a service : stop overhyping technology - Borchert, Heiko (2021)
Today's discussions on conflict stability, force transformation, and proliferation are very techno-centric. This focus misses more important developments, one of which is War as a Service (WaaS). WaaS is about deeply integrating and potentially amalgamating military capabilities among strategic partners, providing actors an option to leapfrog over peers.